Pertumbuhan Aset Sebagai Kunci Utama Dalam Meningkatkan Profitabilitas Bisnis Perusahaan - Annatalia Annatalia; Ana Kadarningsih (Jurnal Akuntan Publik, 2023)
The profitability of a company is used to evaluate or measure whether profits have increased in relation to the seller's total assets and equity capital, whether the company makes a profit, and the profits earned. Company profits are used for the welfare of the company itself. Apart from that, profit also plays an important role in determining the success of a business and as a tool for managerial decision-making. The three objectives of this research are: the effect of asset growth on company profitability; the effect of capital structure on company profitability; and the effect of liquidity on company profitability; In this study, 87 companies registered in oil, gas and geothermal mining were listed on the Indonesia Stock Exchange from 2018 to 2022. Samples taken according to the criteria were collected using a purposive sampling technique. The samples collected included 42 companies, and a total of 210 data were processed. This research analysis uses multiple linear regression analysis, along with descriptive statistical tests, classical assumption tests, and hypothesis tests. The analytical tool used is SPSS version 25. The research results show that only one factor influences the company's profitability, namely asset growth. Capital structure and liquidity, on the other hand, do not affect a company's profitability. Asset growth has a positive impact, while capital structure and liquidity have a negative impact.